2010
DOI: 10.1111/j.1471-0528.2010.02781.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring placental transfusion for term births: weighing babies with cord intact

Abstract: Objective To estimate the volume and duration of placental transfusion at term.Design Prospective observational study.Setting Maternity unit in Bradford, UK.Population Twenty-six term births.Methods Babies were weighed with umbilical cord intact using digital scales that record an average weight every 2 seconds. Placental transfusion was calculated from the change in weight between birth and either cord clamping or when weighing stopped. Start and end weights were estimated using both a B-spline and inspection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(128 citation statements)
references
References 20 publications
5
119
1
3
Order By: Relevance
“…In a term newborn, this transfusion can consist up to one-quarter to one-third of the total neonatal blood volume [65]. In anemia secondary to erythrocyte alloimmunization, a significant increase in hemoglobulin levels at birth was observed, as well as a longer delay between birth and first transfusion, and a decrease in the number of postnatal exchange transfusions, with no notable adverse effects [66,67].…”
Section: Delayed Cord Clampingmentioning
confidence: 99%
“…In a term newborn, this transfusion can consist up to one-quarter to one-third of the total neonatal blood volume [65]. In anemia secondary to erythrocyte alloimmunization, a significant increase in hemoglobulin levels at birth was observed, as well as a longer delay between birth and first transfusion, and a decrease in the number of postnatal exchange transfusions, with no notable adverse effects [66,67].…”
Section: Delayed Cord Clampingmentioning
confidence: 99%
“…1 They found that, for term birth, placental transfusion contributes between one-third and one-quarter of the neonatal blood volume. For most infants, placental transfusion appears to be complete by 2 minutes, but, for some, it continues for up to 5 minutes.…”
mentioning
confidence: 99%
“…The finding that depriving the neonate of a volume of blood [4] resulted in anaemia and iron deficiency six weeks later [5] was not surprising but only recently this anaemia and iron deficiency has been shown to have more significant long term adverse consequences [6]. While a reduction in fine motor skill is not trivial, it is unlikely to be life-threatening.…”
Section: Introductionmentioning
confidence: 99%
“…The original work of Yao [7] was repeated recently using accurate and recording electronic scales [4] and they showed that maximum volume of the placental transfusion can be at least 205 mls. By implication cord clamping within seconds of birth will prevent that volume of blood reaching the neonate.…”
Section: Loss Of Volumementioning
confidence: 99%